Beyond Logframe: Critique, Variations and Alternatives - and Hummelbrunner, Richard (Beyond Logframe; Using Systems Concepts in Evaluation, 2010)
Over the last decades, the Logical Framework Approach (LFA) has become universally known and has assumed a key role for planning and managing development interventions. LFA, however, is not uncontroversial and the approach has been subject to criticism, concerning both its theoretical foundations and practical use. Despite these criticisms LFA’s position has not been fundamentally weakened and while many donors acknowledge its limits and weaknesses, they maintain (some would say impose) its use as a planning and monitoring tool. This chapter reviews some of the experience gained with LFA and outlines major attempts to develop variations – or move beyond it altogether. The first section briefly describes the LFA concept and summarizes the main points of critique. Section 2 then explores some variations which have been developed in response to this critique and to improve LFA as a management tool. Section 3 proposes a systemic alternative to logframe and Section 4 outlines alternatives to LFA which have recently been introduced in German development aid.